Context Matters: Tackling Methane in Livestock Systems for a Sustainable Future - Food Systems for the Future (FSF); Environmental Defense Fund; International Livestock Research Institute (International Livestock Research Institute, 2024)
Summary This dialogue held at the COP29 Action on Food Pavillion on November 20, 2024 aimed to generate consensus and build a diverse coalition across the ruminant meat and complementary protein value chains to align on common policy levers and solution sets that deliver for people, planet, and shared prosperity.